Identification of genes associated with hepatitis B virus infection and breast cancer tumorigenesis and progression - Meirong Zhou; Lili Xu; Haonan Jiang; Lejia Xiong; Shuangping Zhou; Danhua Zhang; Jia Yao; Mei Dai; Lun Li (Biochemistry and Biophysics Reports, 2025)
Background: Studies found that Hepatitis B virus (HBV) infection might be a risk factor for breast cancer tumorigenesis and progression, but the potential mechanism of HBV in breast cancer tumorigenesis and progression was unclear. Our study aimed to understand the interplay between HBV infections and breast cancer via RNA seq data analysis. Methods: We searched GEO databases for related databases. Those datasets that analyzed RNAseq data between breast cancer tissues and normal breast tissues or with prognostic information were included. In vivo cell experiments were conducted to validate the effect of HBV infection on breast cancer cells. Results: We retrieved 20 databases (2206 breast cancer tissues and 860 normal breast tissues) for differentiated expressed genes (DEGs) between breast cancer tissues and normal breast tissues. 54 datasets for survival analysis (14,518 breast cancer patients) were obtained. Higher expression of seven genes (BIRC5, CASP3, CCNA2, CCNE1, CXCL8, CYCS, E2F1) were associated with worse survival. HBV infection may lead to increased expression levels of several key genes in breast cancer cell lines, including CDK2, PCNA, CCNE2, CXCL8, E2F1, and CASP3. Conclusion: HBV might lead to the changes of some genes in breast tissues, which might participate in breast cancer tumorigenesis and progression.